Comparison of coherent optical transmission systems performance by DP-QAM levels - Abdul Gafur; M.S. Islam; Syed Zahidur Rashid (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this paper, we investigated the Coherent Optical Transmission System (COTS) performance for multiple types of DP-QAM levels considering various CW laser input power. We compared the performance of COTS for 100 Gb/s with DP-32QAM, DP-64QAM and DP-128QAM respectively. We also inspected the relationship among Optical Signal to Noise Ratio (OSNR), Error Vector Magnitude (EVM) and Bit Error Rate (BER) which are found in accordance for both simulation curves and constellation diagrams. Results are obtained by experiments with DP-32QAM, DP-64QAM and DP-128QAM modulations techniques at symbol rate of 10 Gsymbol/s, 8.33 Gsymbol/s and 7.142 Gsymbol/s respectively. This work is completely based on simulation in Optisystem simulation setup.